A randomized trial assessing the efficacy, immunogenicity, and safety of vaccination with live attenuated varicella zoster virus-containing vaccines: ten-year follow-up in Russian children - Leyla Namazova-Baranova; Md Ahsan Habib; Michael Povey; Kamilla Efendieva; Olga Fedorova; Marina Fedoseenko; Tatyana Ivleva; Yulia Kovshirina; Julia Levina; Artem Lyamin; Ludmila Ogorodova; Olga Reshetko; et al. (Taylor & Francis Group, 2022)
In Russia, a universal varicella vaccination (UVV) program has not been implemented, and varicella vaccination coverage is low. We assessed the efficacy, antibody persistence, and safety of one- and two-dose varicella vaccination schedules in Russian children with a ten-year follow-up period, as part of an international phase IIIB, observer-blind, randomized, controlled trial (NCT00226499). Children aged 12-22 months were randomized (3:3:1) to receive two doses of tetravalent measles-mumps-rubella-varicella vaccine (V2 group), one dose trivalent measles-mumps-rubella (MMR) vaccine and one dose of varicella vaccine (V1 group), or two doses of MMR vaccine (V0 [control] group), 42 days apart. Main study outcomes were: vaccine efficacy (VE) against confirmed varicella cases, anti-varicella zoster virus (VZV) seropositivity rates and geometric mean concentrations, and reporting of (serious) adverse events ([S]AEs). The total vaccinated cohort in Russia comprised 1000 children; 900 were followed up until study end (year [Y] 10). VE estimates against confirmed varicella (Y10) were 92.4% in the V2 group and 74.7% in the V1 group. Anti-VZV seropositivity rates remained ≥99.4% in the V2 group and ≥89.7% in the V1 group from day 42 post-vaccination 2 until Y10. Occurrence of (un)solicited AEs and SAEs was similar across groups and confirmed the safety profile of the vaccines. No vaccination-related SAEs or deaths were reported. These results are consistent with the global trial results, i.e., the highest VE estimates observed following the two-dose schedule compared to the one-dose schedule. These data may inform decision-making related to potential implementation of a UVV program.